Welfare states and gender inequality in Central and Eastern Europe. Continuity and post-socialist transformation in the EU Member States (Brussels, 2010)
"This book edited by Christina Klenner and Simone Leiber and first published in German, focuses on developments in the welfare states of the ten Central and Eastern European EU member states in the transformation process some 20 years after the end of state socialism. It also explores the shifts in gender relationships and inequalities, and tries to depict the interdependencies between these two processes. The contributors to this volume tackle the following main questions: how far are welfare states and gender regimes in these countries comparable with the types found in Western and Southern Europe? To what extent were traditional institutions and practices preserved under the new circumstances resulting from the system change? How have gender relations been affected by EU accession and welfare state change through the transformation process? A further focus, as yet subject to insufficient systematic research, is the effects on gender inequality of reforms in different social policy fields. "